Halide Ion Migration and its Role at the Interfaces in Perovskite Solar Cells. Issue 46 (23rd November 2021) - Kim, Minjin; Jun, Haeyeon; Lee, Heejae; Nahdi, Hindia; Tondelier, Denis; Bonnassieux, Yvan; Bourée, Jean‐Éric; Geffroy, Bernard
Abstract: Lead‐halide perovskite solar cells (PSCs) based on unusual semiconductors made with ions, have shown impressive improvement in photovoltaic performance in few years exceeding nowadays 25 % power conversion efficiency. However, PSCs suffer from a lack of stability and show significant hysteresis in current‐voltage curves, which are impeding commercialization. We confirmed the importance of halide ion migration in the hysteresis effect which has direct consequences on device efficiency. Using impedance spectroscopy, in addition to the geometrical capacitance found at high frequency for fresh samples without bias, we observed a second capacitance at low frequency after ageing or under bias. This second capacitance is interpreted as a charge accumulation layer at interfaces, which can be promoted by the presence of grain boundaries. Through glow‐discharge optical emission spectroscopy elemental depth profiles, we found that under dark conditions, iodide ions diffuse through the electron transport layer versus ageing time. These ions interact chemically with the front‐end electrode after four weeks and form silver iodide. Abstract : Accumulation of halide ions/vacancies at the interfaces revealed by GD‐OES and impedance spectroscopy measurements in lead‐halide perovskite solar cells. Grain boundaries promote ions migration and increase with ageing time.